Robust Control with Finite Time Convergence for Flexible Spacecraft Attitude Tracking - Kotsamran*, Kanoktip; Pukdeboon, Chutiphon (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
The problem of attitude tracking for a flexible spacecraft is studied in this paper. A finite-time sliding mode controller is applied to quaternion-based attitude control for tracking maneuvers with external disturbances. The proposed sliding mode control law is developed by using a terminal sliding mode control algorithm which is able to guarantee finite time reachability of given desired attitude motion of a flexible spacecraft. By using the second method of Lyapunov and terminal sliding mode control concepts, stability of the closed-loop system can be achieved in finite time. An example of multiaxial attitude maneuvers is presented. Simulation results are included to demonstrate and verify the usefulness of the developed controller. Keywords: Attitude tracking control, flexible spacecraft, terminal sliding mode, finite time convergence E-mail: kanoktipk@gmail.com